2006
DOI: 10.1210/jc.2005-2679
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, Function, and Dysregulation of Endocannabinoids in Models of Adipose and β-Pancreatic Cells and in Obesity and Hyperglycemia

Abstract: Peripheral endocannabinoid overactivity might explain why CB(1) blockers cause weight-loss independent reduction of lipogenesis, of hypoadiponectinemia, and of hyperinsulinemia in obese animals and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

69
768
15
34

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 607 publications
(886 citation statements)
references
References 34 publications
69
768
15
34
Order By: Relevance
“…Matias et al 60 reported that a CB1R agonist stimulates glucose-dependent insulin secretion (GDIS) in rat insulinoma RIN-m5F cells. These results would predict that inverse agonists should inhibit glucose-dependent insulin release.…”
Section: Pancreatic Isletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matias et al 60 reported that a CB1R agonist stimulates glucose-dependent insulin secretion (GDIS) in rat insulinoma RIN-m5F cells. These results would predict that inverse agonists should inhibit glucose-dependent insulin release.…”
Section: Pancreatic Isletsmentioning
confidence: 99%
“…These results would predict that inverse agonists should inhibit glucose-dependent insulin release. Given that rimonabant has been shown to improve glycemic control in diabetic patients, the prediction of Matias et al 60 is counter-intuitive as many anti-diabetic agents such as GLP-1 are known to stimulate GDIS.…”
Section: Pancreatic Isletsmentioning
confidence: 99%
“…Many of the biological actions of the ECS are mediated through G‐protein‐coupled cannabinoid type 1 (CB1R) and type 2 (CB2R) receptors which can be activated by several endogenous ligands, including anandamide (AEA) and 2‐arachidonoylglycerol (2‐AG). Importantly, ECS dysregulation has been linked to abdominal obesity and other risk factors for type 2 diabetes (Engeli et al ., 2005; Osei‐Hyiaman et al ., 2005; Matias et al ., 2006). For example, genetic and diet‐induced obese animal models display elevated endocannabinoid levels in the hypothalamus and peripheral tissues (Di Marzo et al ., 2001; Osei‐Hyiaman et al ., 2005; Matias et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, ECS dysregulation has been linked to abdominal obesity and other risk factors for type 2 diabetes (Engeli et al ., 2005; Osei‐Hyiaman et al ., 2005; Matias et al ., 2006). For example, genetic and diet‐induced obese animal models display elevated endocannabinoid levels in the hypothalamus and peripheral tissues (Di Marzo et al ., 2001; Osei‐Hyiaman et al ., 2005; Matias et al ., 2006). Furthermore, increased circulating levels of AEA and 2‐AG, as well as elevated levels of 2‐AG within visceral adipose tissue, have been reported in obese and/or hyperglycaemic type 2 diabetic patients (Bluher et al ., 2006; Matias et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation